ANTIMICROBIAL AND ANTIOXIDANT EFFECT OF NATURAL EXTRACTS FROM LEAVES, ROOT, STEM AND FLOWERS OF BACCHARIS LATIFOLIA FROM ECUADOR - BAYAS-MOREJON, FAVIAN; TIGRE, ANGELICA; RAMON, RIVELINO; YANEZ, DANILO (International Journal of Current Pharmaceutical Research, 2020)
Objective: The increase in chronic and degenerative diseases and the use of synthetic antioxidants such as (butylated hydroxyanisole (BHA) or butylated hydroxytoluene (BHT)) are being restricted because they can be considered carcinogenic. Therefore, there is a growing interest in the search for natural antioxidants, especially from plants, due to their content in different bioactive compounds, such as antioxidants and antimicrobials. To evaluate the antibacterial and antioxidant activity of Baccharislatifolia extracts. Methods: For the determination of the antimicrobial activity of extracts of leaves, root, stem and flowers of Baccharislatifolia (Bl), the disk plate diffusion method was used, the strains of Listeria, Salmonella and E. coli were studied; antibiotics Penicillin G and Ciprofloxacin were the controls. For the antioxidant activity, a solution of H2O2 (Abs at 230 nm) was prepared in Potassium Phosphate Monobasic-Sodium Hydroxide buffer. Results: The antimicrobial activity against Listeria and Salmonella, showed that the extracts of leaves and flowers were more effective with inhibition zones>15 mm and>20 mm respectively. In front of E. coli, the extracts of flowers and stem were the best with zones>7.0 mm. Antibiotics studied inhibited the development of Listeria and Salmonella. However, E. coli isolates were resistant. In the antioxidant activity, the flower extract of Bl in 60 mg/ml presents a higher effect with 47.25%. Conclusion: Bl extracts from leaves and flowers were more efficient both in their antimicrobial and antioxidant capacity.